A study of the customer perceptions and attitude towards counterfeit products / Sharon Joel Jimbai - Joel Jimbai, Sharon (2015)
The purpose of the research is to test the customer perception and attitude towards counterfeit products based on attitudes, subjective norms and price quality inference. The sample in this research was the staff of AARGYP Scientific and people who are working along Jalan Keretapi that had knowledge and experience about counterfeit products. A survey of 132 respondents was conducted in AARGYP Scientific Sdn Bhd and offices along Jalan Keretapi, Kuching. Reliability analysis and descriptive statistics test were used to test the objective obtain and research question. It is discovered that customer attitudes, subjective norms and price quality inference are the independent variables that strongly influence customer perception and attitudes towards counterfeit products. By having a better understanding of consumers’ behavioural intentions of buying counterfeit products, the manufacturers and marketers of the genuine brand products can make better marketing strategies to entice the consumer to buy the original products and not the counterfeit version. Theoretical contribution of this study is an extension of knowledge of consumers’ attitudes with regards to counterfeit products.